PENERAPAN STRATEGI PAIKEM DALAM MENINGKATKAN PEMBELAJARAN PAI DI SMK SUMBER BUNGA SLETRENG KAPONGAN SITUBONDO - Rusdi Rusdi (Research Institute and Community Engagement of IAIN MADURA, 2018)
There are many components that influence the islamic education teaching learning process, one of which is “the method of Religious Education”. Nowadays, the method of Islamic Education is still using the old method such as giving speech, memorizing and demonstrating worship practices which look very empty. It is obvious that this kind of method makes the students bored, tired and unmotivated in learning Religion. Alternatively, to increase the quality of education, teacher can apply the PAIKEM strategy (active, inovative, creative, effective, and happy learning) in the Islamic Education teaching learning process. It is expected through PAIKEM strategy, the teacher and students become more active and creative in the process of teaching and learning. The conclusion of this research is the application of PAIKEM strategy can increase the Islamic Education teaching learning process in SMK Sumber Bunga Situbondo from the process of planning, acting, and evaluating. Factors that support the application of PAIKEM strategy are the teachers’ ability in applying PAIKEM and the students’ readiness in studying. The weaknesses of the application of PAIKEM strategy are the infrastructure, environment and the time allocation.